Azacalix[3]triazines: A Substructure of Triazine‐Based Graphitic Carbon Nitride Featuring Anion‐π Interactions. (15th June 2021) - Gong, Hao; Zhang, Cheng; Ogaki, Takuya; Inuzuka, Hiroyuki; Hashizume, Daisuke; Miyajima, Daigo
Abstract: Graphitic carbon nitride (GCN) has garnered broad research interest due to its unique catalytic properties. However, GCN, prepared by general methods, possesses myriad structural defects and it has been difficult to elucidate their intrinsic physical properties. We report the development of azacalix[3]triazines (AC3Ts), a substructure of triazine‐based GCN (Tz‐GCN). Despite the electron‐deficient natures of triazine, AC3Ts capture protons as organic superbases. We reveal the unique anion‐π interactions of AC3Ts that alters the ionization potentials of AC3Ts. To the best of our knowledge, these features have not yet been recognized for Tz‐GCN. These unveiled features of AC3Ts are expected to expand the usage scope and possibilities for GCNs. Abstract : Graphitic carbon nitride (GCN) has drawn considerable interest since the discovery of its metal‐free photocatalytic properties. The synthesis of a substructure of triazine‐based GCN (Tz‐GCN), azacalix[3]triazines, is reported. The material exhibits super strong basicity as well as anion‐π interactions.